Development of Lightboard-Based Flipped Classroom Learning Videos on Parabolic Motion Materials - Arman La Aca; Dwi Sulisworo (Jurnal Pendidikan Fisika, 2020)
This study aims to produce lightboard-based flipped classroom learning videos on parabolic motion materials that are suitable for use as learning media. This type of research is ADDIE, which aims to produce a products with product validity from material experts, media experts, and physics teachers. The assessment of the feasibility level of the material expert was 94%, media expert 91.5%, and physics teacher 95%. The average level of feasibility of this learning video is 94%. The results of the assessment of 32 students as a feasibility trial for video lightboard obtained results from aspects of the material 88.15%, the effect on learning 91.41%, audiovisual display 90.10%, and language 90.36%. The average result of the feasibility of a video lightboard trial was 90.01%. From the results of the feasibility assessment it can be concluded that this learning video is categorized as very appropriate to be used as a learning media. This research can be used as a reference in producing effective and efficient learning media.